1998
DOI: 10.1128/mcb.18.3.1379
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the p85/p110 Phosphatidylinositol 3′-Kinase: Stabilization and Inhibition of the p110α Catalytic Subunit by the p85 Regulatory Subunit

Abstract: We propose a novel model for the regulation of the p85/p110␣ phosphatidylinositol 3-kinase. In insect cells, the p110␣ catalytic subunit is active as a monomer but its activity is decreased by coexpression with the p85 regulatory subunit. Similarly, the lipid kinase activity of recombinant glutathione S-transferase (GST)-p110␣ is reduced by 65 to 85% upon in vitro reconstitution with p85. Incubation of p110␣/p85 dimers with phosphotyrosyl peptides restored activity, but only to the level of monomeric p110␣. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
451
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 467 publications
(477 citation statements)
references
References 55 publications
25
451
0
1
Order By: Relevance
“…The observed reduction of p110β expression may also be attributed to the reduced expression of p85. Previous studies have suggested that the interaction between the catalytic and regulatory subunits is important for the stability of the p110 catalytic subunit [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The observed reduction of p110β expression may also be attributed to the reduced expression of p85. Previous studies have suggested that the interaction between the catalytic and regulatory subunits is important for the stability of the p110 catalytic subunit [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In p110*, the iSH2 domain of p85a is fused to the N-terminus of p110a, 26 thus stabilizing monomeric p110 against thermal denaturation at 371. 27 Its in vivo activity is much weaker than the membrane-localizing forms, 26 but is ideally suited for our purpose, which was to use p110* to augment PI3-kinase activity in DKI cells stimulated by CSF-1. Four independent DKI clones transfected with p110* were selected for further analysis.…”
Section: Csf-1-dependent Mitogenesis Requires Both Erk and Pi3-kinasementioning
confidence: 99%
“…3). The regulatory subunits have two major functions: they stabilize the catalytic subunits against thermal denaturation, and they maintain the catalytic subunit in an inhibited, low activity state (4,5).…”
mentioning
confidence: 99%
“…Class IA PI 3-kinases, which produce PI [3,4,5]P3 in intact cells (2), are obligate heterodimers of a regulatory subunit (p85␣, p85␤, p55␣, p50␣, or p55␥) and a catalytic subunit (p110␣, p110␤, or p110␦) (reviewed in ref. 3).…”
mentioning
confidence: 99%